2019
DOI: 10.1016/j.jclepro.2019.118198
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to smart waste management for a circular economy in China

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
190
2
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 320 publications
(203 citation statements)
references
References 68 publications
4
190
2
7
Order By: Relevance
“…Current configurations of the supply chain must be redesigned to implement the exchange of waste and industrial by-products considering the principles of the circular economy [56]. This problem involves "a variety of stakeholders, demands behavioral changes, and requires a complete rethinking of the current waste management systems and the dominant linear economic model" [82] (p. 1). Circular thinking must be applied at all stages of the supply chain and go beyond the boundaries of the sector [27].…”
Section: Relational Structurementioning
confidence: 99%
See 2 more Smart Citations
“…Current configurations of the supply chain must be redesigned to implement the exchange of waste and industrial by-products considering the principles of the circular economy [56]. This problem involves "a variety of stakeholders, demands behavioral changes, and requires a complete rethinking of the current waste management systems and the dominant linear economic model" [82] (p. 1). Circular thinking must be applied at all stages of the supply chain and go beyond the boundaries of the sector [27].…”
Section: Relational Structurementioning
confidence: 99%
“…Intelligent waste management systems involve both infrastructure and management aspects, but also aspects related to the behavior of citizens, product designers, producers, and policy makers. The functions in this system consider from the design of the products or services to the end-of-life management [82,95]. The involvement of the main actors is essential to control or to decrease waste generation [36,82].…”
Section: Adaptation Of Logistics and Organizational Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…The barriers were different depending on the business model of the company, with internal and external barriers identified and critical challenges related to corporate externalities. Developing a more circular approach to waste management in China identified key barriers such as a lack of regulatory pressure, lack of environmental education, lack of concern for environmental protection and low market pressures and demand for circularity [39]. Other research has also confirmed that the primary barrier to developing a circular economy is uncertainty over the potential financial and operational effects on a company [40].…”
Section: Literature Review Of Research On Barriers To a Circular Economymentioning
confidence: 99%
“…Based on this previous recent work and from analysing the barriers to specific materials and end of life products, the barriers identified by other workers have been re-grouped thematically [29,37,[39][40][41][42]. This has produced a set of nine primary barriers, and these have been used in the assessment method developed in this work.…”
Section: Development Of Barrier Criteriamentioning
confidence: 99%